Concussion Care Manual : a Practical Guide. - Brody, David L. (Oxford University Press, USA, 2014)
This is a practical manual for clinicians who take care of patients with concussions. The long-term effects of concussions are an increasingly recognized problem in the medical community and by the general public. Most people recover well from concussions, but a substantial minority does not. However, most clinicians do not have specific training in how to evaluate and treat concussion patients who do not make a rapid and complete recovery. This manual, based on the experience of the director of the concussion clinic at Washington University in St Louis, provides specific step-by-step guidance.